Evaluation of Understanding of Safety, Health and Safety (K3) Using the Method Cumulative Voting (case Study of PT. Kencar Sukses Investama) - Wildansyah Rokhmana Putra; Rani Purbaningtyas; Eko Prasetyo (JEECS (Journal of Electrical Engineering and Computer Sciences), 2020)
Every employee who works must understand safety in order to create a conducive work environment and Zero Accident. This study aims to create an Evaluation System for Understanding Safety, Health and Safety (K3) by using the Cumulative Voting Method so that it can optimize the quality of K3 in the company to be more effective and efficient. From the application trial results obtained the results of the validity test between manual data and application data have a difference in the results because the manual workmanship is calculated with a manual averagewithout any cumulativevalue of each item being tested. Application of K3 Comprehension Evaluation with Cumulative Voting Method can also prevent or minimize user input errors.